Pembuatan Biodiesel Dari Biji Kapuk (Ceiba Pentandra) Dengan Katalis Padat H-Zeolit - Afrielyanda H; Syaiful Bahri; Khairat Khairat (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Biodiesel as alternative diesel fuel made from renewable biological resources, such as vegetable oils and animal fats. In Indonesia, the fuel consumption is increasing every year, so often there is a shortage of fuel. Therefore, the latest innovations necessary to produce alternative energy such as biodiesel. In this research, the conversion of cotton seed oil to biodiesel was performed by using catalyst "H-zeolite". First, cotton seed is dried whole day in order to reduce the water content and then extracted using a solvent n-hexane. Then separate the solvent with oil until the oil obtained pure. Afterwards, cotton seed oil is converted into biodiesel using transesterification reaction with methanol as reagent and H-zeolite catalyst. Transesterification reaction is carried out at 600C temperature operating conditions, the stirring speed of 200 rpm and reaction time of 200 minutes. To get the maximum biodiesel, using variation the molar ratio of cotton seed oil and methanol (1: 3; 1: 6; 1: 9), the variation of the catalyst (1%, 2%, 3% w/w) were performed in this research . The results showed maximum biodiesel conversion of about 79.35%, the molar ratio of cotton seed oil and methanol 1: 9 and catalyst 2% of the total amount of oil. Based on the analysis of physical properties of biodiesel has a density of 859 kg / m3, 5.60 cSt viscosity, acid number 0.561 mg-KOH / g sample. In addition, analysis of the chemical properties of biodiesel from cotton seed oil using GC - MS.Keywords : Cotton seed oils, Biodiessel, H-zeolit catalyst, Transesterification reaction.